2007
DOI: 10.1084/jem.20070601
|View full text |Cite
|
Sign up to set email alerts
|

Thymic emigration revisited

Abstract: Conventional αβ T cell precursors undergo positive selection in the thymic cortex. When this is successful, they migrate to the medulla and are exposed to tissue-specific antigens (TSA) for purposes of central tolerance, and they undergo maturation to become functionally responsive T cells. It is commonly understood that thymocytes spend up to 2 wk in the medulla undergoing these final maturation steps before emigrating to peripheral lymphoid tissues. In addition, emigration is thought to occur via a stochasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
273
2
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(304 citation statements)
references
References 37 publications
27
273
2
2
Order By: Relevance
“…Additionally, our multiple regression analyses show a significant statistical dependency of the FOXP3 1 DP and SP populations, further supporting their direct precursor-product association. The numerical difference in those populations may be explained by a significant commitment to the Treg-cell lineage at the DP stage together with an accumulation of FOXP3 1 SP cells prior to their exit, due to the time-lag incurred by maturation of cells in the thymic medulla [43]. Recent murine studies have also demonstrated the possibility of Treg-cell generation in the cortex, followed by rapid migration into the medulla, where they mature [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our multiple regression analyses show a significant statistical dependency of the FOXP3 1 DP and SP populations, further supporting their direct precursor-product association. The numerical difference in those populations may be explained by a significant commitment to the Treg-cell lineage at the DP stage together with an accumulation of FOXP3 1 SP cells prior to their exit, due to the time-lag incurred by maturation of cells in the thymic medulla [43]. Recent murine studies have also demonstrated the possibility of Treg-cell generation in the cortex, followed by rapid migration into the medulla, where they mature [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we confirmed these results by demonstrating H2BeGFP loss during thymic exit solely for CD8 + and not for CD4 + RTEs. It was speculated that CD8 + thymocytes in RAG2p-GFP transgenic mice showed lower GFP levels because their DP to SP transition took longer time than in CD4 + thymocytes (19). In this study, we observed that decline of H2BeGFP reporter intensity was greater in CD8 + compared with CD4 + T cells.…”
Section: Discussionmentioning
confidence: 47%
“…Earlier studies using these methods suggested intrathymic expansion of mature thymocytes before export to the periphery (17). More recently, BAC-transgenic mice with multiple copies of GFP under the control of the Rag2 promoter (18) were used as a genetic tool to monitor the dynamics of thymic maturation, emigration (19), and to directly identify recent thymic emigrants (RTEs) (20,21). In this Rag2p-GFP system, GFP-reporter transcription terminates after Tcra rearrangement in DP cells, but GFP fluorescence is detectable in peripheral T cells because of the considerable halflife of GFP in mouse T cells estimated to range between 16 and 18 h (20) and 54 and 56 h (19).…”
Section: P Roliferation Of Ab T Cells Occurs At Different Stages Dur-mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the level of TRA expression per cell is always lower in mTEC than in the corresponding tissue [30]. Third, the average residence time of mature thymocytes of 4 to 5 days is shorter than previously assumed [31,32]. Nevertheless, deletion of monoclonal or polyclonal T-cell repertoires specific for ectopically expressed (neo) self-antigens is highly efficient [33,34].…”
Section: Spatial Is Expressed In Mature Medullary Thymic Epithelial Cmentioning
confidence: 96%